2015
DOI: 10.1159/000440884
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Protective Factors for Small Intestine Neuroendocrine Tumors: A Prospective Case-Control Study

Abstract: Background: The incidence of small intestine neuroendocrine tumors (SI-NETs) is increasing, but few studies have investigated risk factors for their occurrence, suggesting that family history (FH) of any cancer, smoking and previous cholecystectomy are associated with an increased risk. Such studies investigated small series or examined cancer registries without direct interviews. Aim: We therefore aimed at clarifying risk and protective factors for the occurrence of sporadic SI-NETs. Subjects and Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 34 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…A recent Italian study [30] identified a familial history of colorectal cancer or breast cancer and a personal history of smoking and alcohol abuse as possible risk factors for the development of NENs of the small intestine, whereas another study has suggested that hypercholesterolemia, hyperferritinemia, metabolic syndrome, and a history of cancer among first-degree relatives may increase the risk of rectal NENs [32] . In particular, as regards rectal neuroendocrine tumors, a further study highlighted that young age (<50 years), male gender, alcohol consumption, and low HDL circulating levels are among the possible risk factors [33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Italian study [30] identified a familial history of colorectal cancer or breast cancer and a personal history of smoking and alcohol abuse as possible risk factors for the development of NENs of the small intestine, whereas another study has suggested that hypercholesterolemia, hyperferritinemia, metabolic syndrome, and a history of cancer among first-degree relatives may increase the risk of rectal NENs [32] . In particular, as regards rectal neuroendocrine tumors, a further study highlighted that young age (<50 years), male gender, alcohol consumption, and low HDL circulating levels are among the possible risk factors [33] .…”
Section: Discussionmentioning
confidence: 99%
“…NENs can be sporadic, but there are also some familial syndromes with a high penetrance of NENs, such as multiple endocrine neoplasia type 1. Little is known about the potential risk factor for these types of tumors [30] . In particular, the possible association between plasma 25-OHvitD deficiency and neuroendocrine tumors is largely unexplored.…”
mentioning
confidence: 99%
“…A meta-analysis of all case-control studies undertaken between 1994 and 2014 comprising 4,144 cases of combined SBNEN and PanNEN and 108,303 controls identified several candidate risk factors for SBNEN and PanNEN [22]. A family history of any cancer, "ever smoking" (but not specifically heavy smoking) [23] and gall-bladder disease/cholecystectomy were associated with ∼1.5-fold increased risk of developing SBNEN [24]. Alterations in bile homeostasis are known to modify bile-salt catabolite production, alter the gut microbiota and modify the mucosal immune environment.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Another study, combining family cancer datasets from Sweden and Finland, provided specific evidence of familial associations in individuals with small intestine carcinoid tumors: siblings of individuals with small intestine carcinoid tumors had a 30-fold higher risk of developing the same condition, and parents or children a 10-fold increased risk (Kharazmi et al 2013). A recent study that focused on families with small intestine carcinoid tumors revealed the presence of multifocal and independent tumors arising within the small intestine, consistent with the presence of an inherited susceptibility gene (Sei et al 2016). Inherited mutations in the gene IPMK were identified in one such family, though not in other families (Sei et al 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, no clearly established environmental risk factors for neuroendocrine tumors have been identified. Case control studies have provided conflicting data regarding potential links between the development of neuroendocrine tumors and smoking or other exposures (Hassan et al 2008 a ,b, Rinzivillo et al 2015). An inherited basis for presumed “sporadic” neuroendocrine tumors has been suggested by evidence of familial clustering of neuroendocrine tumors described in both case series and population-based studies.…”
Section: Introductionmentioning
confidence: 99%